2022
DOI: 10.53730/ijhs.v6ns2.6715
|View full text |Cite
|
Sign up to set email alerts
|

study of the correlation between vitamin B12, folic acid and ferritin with thyroid hormones in hypothyroidism

Abstract: Background: Thyroid hormones are required for normal development as well as regulating metabolism in the adult. Thyroid gland disorders are the second most abundant endocrinal disorders after diabetes. A decreased thyroid hormone adversely affects erythropoietic system causes anaemia. Aim: The Aim and objective of the study was to compare the vitamin B12, Folate and Ferritin with thyroid hormones in hypothyroidism. Methods: In the present study, total 350 samples were included in which 175 were hypothyroid pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…The results as shown in Table 2 agreed with [31] and [36] whom recorded an increasment in prolactin levels in hypothyroid patient compared to control group, this increasment is due to high levels of TRH in hypothyroid stimulates the lactotrophs in pituaitry gland which leads to rise its level in the blood [37 Whin we studied the level of vitamin B12 the results shows a significant decrease in Vitamin B12 level (P ≤ 0.027) in hypothyroid patients compared to control group as shown in Table 3. This findings agreed with [38] and [39] whom recorded a decreasement in Vitamin B12 levels in hypothyroid patients compared to control group and there is no results disagreed with this findings, the cause of Vitamin B12 deficiency in hypothyroidisim is due to the malabsorption of Vitamin B12 in hypothyroid patient [40], Jaya and his assistant found that 1/3 of hypothyroid patient had antibody against parietal cell that secreted intrinsic factor which help to well absorb the Vitamin B12 [41].…”
Section: Resultssupporting
confidence: 89%
“…The results as shown in Table 2 agreed with [31] and [36] whom recorded an increasment in prolactin levels in hypothyroid patient compared to control group, this increasment is due to high levels of TRH in hypothyroid stimulates the lactotrophs in pituaitry gland which leads to rise its level in the blood [37 Whin we studied the level of vitamin B12 the results shows a significant decrease in Vitamin B12 level (P ≤ 0.027) in hypothyroid patients compared to control group as shown in Table 3. This findings agreed with [38] and [39] whom recorded a decreasement in Vitamin B12 levels in hypothyroid patients compared to control group and there is no results disagreed with this findings, the cause of Vitamin B12 deficiency in hypothyroidisim is due to the malabsorption of Vitamin B12 in hypothyroid patient [40], Jaya and his assistant found that 1/3 of hypothyroid patient had antibody against parietal cell that secreted intrinsic factor which help to well absorb the Vitamin B12 [41].…”
Section: Resultssupporting
confidence: 89%
“…[20] Level of Vitamin B12 was significantly decreased in Hypothyroidism in comparison to normal individual. Folate was significantly decreased in Hypothyroidism as compared to normal [13].…”
Section: Discussionmentioning
confidence: 78%
“…Low serum ferritin is one of the most common reasons of thyroid dysfunction. [12,13] The prevalence of vitamin B12 insufficiency rises with age. Patients with vitamin B12 insufficiency with hypothyroidism typically experience fatigue, weakness, poor memory retention, itching, and loss of feeling.…”
Section: Introductionmentioning
confidence: 99%
“…If iron is tested then total iron binding capacity is checked with lower hemoglobin in the blood [82]. Though the lower level of iron is directly related with anemia and ferritin as it is its storage form, mostly, iron test is enough for confirming deficiency as a complication [83,84]. The TIBC test is as same as iron and ferritin so the normal range in this test is 240 to 450mcg/dL [85].…”
Section: Other Testsmentioning
confidence: 99%